Legitimacy on Inter-Faith Marriages: An Analysis of the Role of Religious Councils on the Legal Policy in Indonesia - Rosdiana Rosdiana; Ummu Hanah Yusuf Saumin; Masayu Mashita Maisarah (AHKAM : Jurnal Ilmu Syariah, 2019)
The legal vacuum for of inter-faith marriage is one of the unresolved issues in Indonesia, especially with regard to civil rights. Indonesia’s Marriage Law No. 1 of 1974 has not accommodated the legal policy of marriage between different religions. Moreover, there are some different views between religious leaders on the permissibility of the inter-faith marriage. This study attempts to analyse the relations between Indonesia’s Religious Councils and the legal policies on inter-faith marriages. Data was collected through observation and semi-structured interviews with the representatives of Indonesia’s religious councils from six religions. It finds that Indonesia’s Religious Councils have no role by any means in the formation of legal policies related to inter-faith marriage in Indonesia since the Marriage Law had been created before the Religious Councils established. Regarding the legitimacy of inter-faith marriage, the religious leaders offered conflicting statements. Several religious leaders still decided to stay with the prohibition of interfaith marriage based on the popular religious traditions and the constitutional realm. Albeit religious leaders favour or disfavour inter-faith marriage, the practice is still widely flourished and rapidly increased. This observable fact should be an important reason for the Constitutional Court either to grant or deny the practices of inter-faith marriage in Indonesia. Terkait hak-hak sipil, terdapat kekosongan  landasan hukum dalam kasus perkawinan beda agama di Indonesia. Undang-Undang Perkawinan Indonesia No. 1 Tahun 1974 tidak mengakomodasi kebijakan hukum perkawinan beda agama. Selain itu, ada perbedaan pandangan antara para pemimpin agama tentang diizinkannya pasangan dari agama yang berbeda, misalnya dalam hal peninjauan materi Pasal 2 ayat (1) UU Perkawinan. Oleh karena itu, penelitian ini menganalisis hubungan antara Dewan Agama Indonesia dan kebijakan hukum tentang pernikahan antar agama. Sumber data penelitian ini adalah observasi dan wawancara semi-terstruktur dengan perwakilan dari Dewan Agama Indonesia dari lima agama yang diakui di Indonesia. Penelitian ini menemukan bahwa Dewan Agama Indonesia tidak memiliki peran apa pun dalam penentuan kebijakan hukum pernikahan beda agama. Hal ini  karena UU Perkawinan telah dibuat sebelum adanya Dewan Agama. Dalam topik legitimasi  pernikahan lintas agama, para pemimpin agama menyatakan pernyataan yang bertentangan. Sejumlah pemimpin agama masih memutuskan melarang  pernikahan antar agama berdasarkan tradisi keagamaan populer dan ranah konstitusional sedangkan bebera  lainnya memberikan sebaliknya. Meskipun belum ada kesepakatan  para pemimpin agama tentang  pernikahan antaragama, praktik ini masih terjadi bahkan meningkat pesat. Fakta ini harus menjadi alasan penting bagi Mahkamah Konstitusi untuk memberikan atau menolak praktik pernikahan antaragama di Indonesia.